Effect of diabetes on mortality and length of hospital stay in patients with renal or perinephric abscess - Ming-Chung Ko; Allen Wen-Hsiang Chiu; Chih-Ching Liu; Chih-Kuang Liu; Lin-Chung Woung; Lai-King Yu; Chung-Yi Li (Clinics, 2013)
OBJECTIVES: We compared the risk of in-hospital mortality and the length of hospital stay between diabetic and non-diabetic patients hospitalized for renal or perinephric abscess. METHOD: The data analyzed in this study were retrieved from Taiwan's National Health Insurance claims. The risk of in-hospital mortality and the length of hospital stay were compared between 1,715 diabetic patients, hospitalized because of renal or perinephric abscess in Taiwan between 1997 and 2007, and a random sample of 477 non-diabetes patients with renal or perinephric abscess. RESULTS: The in-hospital mortality rates from renal or perinephric abscess for the diabetic patients and the non-diabetic patients were not different, at 2.3% and 3.4%, respectively. However, diabetes was significantly associated with a longer length of hospital stay among patients with renal abscess, by 3.38 days (95% confidence interval [CI]: 1.59-5.17). CONCLUSIONS: Diabetes does not increase the risk of in-hospital mortality from renal or perinephric abscess. Nevertheless, appropriate management of patients with diabetes and concurrent renal or perinephric abscess is essential to reduce the length of hospital stay.